Perancangan Knowledge Management System Kegiatan Karyawan Berbasis Android - Khairunisa Nabila Salamah Ongso; Rita Wahyuni Arifin; Harjunadi Wicaksono; Sigit Setiawan (Prosiding SISFOTEK, 2024)
Museum is an institution that functions to protect, develop, utilize collections, and communicate them to the public. To carry out these functions properly, all employees in the Museum unit must be aware of all existing activity information. Problems experienced in the internal environment of employees at the Museum are in the form of activity information management and dissemination. The delivery of activity information for some employees still uses manual methods, such as writing on the blackboard, communicating verbally, and using google docs. As well as information sources that are not centralized in one source can hinder the change of tacit knowledge to explicit, limiting the accessibility and mobility of existing information. Therefore, this research aims to design a Knowledge Management System application for internal employee activities based on android to overcome these obstacles. A solution is proposed to help employees get the latest information quickly and efficiently. The information system was developed using the User Centered Design method which enables a development process that focuses on the end user. The results of this application research get 85% overall in the test, so this Knowledge Management System application can make a positive contribution to employee productivity and collaboration and advance service quality in the museum work environment.